Glycosylated cationic block co-beta-peptide as antimicrobial and anti-biofilm agents against Gram-positive bacteria - Zhang, Kaixi (Nanyang Technological University, 2020)
Antimicrobial resistance to last-resort antibiotics is a serious and chronic global problem. The treatment of bacterial infection is further hindered by the presence of biofilm and metabolically inactive persisters. Methicillin-resistant Staphylococcus aureus (MRSA) is a major pathogen causing high rates of mortality and morbidity. We report the synthesis of a new enantiomeric block co-beta-peptide, poly(amido-D-glucose)-block-poly(beta-L-lysine)) (PDGu-b-PBLK), with high yield and purity by one-shot one-pot anionic-ring opening (co)polymerization (AROP). The co-beta-peptide is bactericidal against replicating as well as biofilm and persisters MRSA, and also disperses biofilm biomass. It is active towards both community-acquired and hospital-associated MRSA strains which are resistant to multiple drugs including vancomycin and daptomycin. Its antibacterial activity is superior to vancomycin in established MRSA murine and human ex vivo skin infection models, with no acute in vivo toxicity in repeated dosing in mice at above therapeutic levels. The bacteria-activated surfactant-like effect of the copolymer, resulting from contact with bacterial envelope, induces high bactericidal activity with low toxicity and good biofilm dispersal. This new class of non-toxic molecule, effective against all bacterial sub-populations, has promising clinical potential. Besides Staphylococci, biofilms of many other Gram-positive pathogens (including Streptococci, Enterococci) are closely associated with recalcitrant infections and poor clinical outcomes of standard antibiotic treatment. Moreover, many biofilm-associated infections are polymicrobial, and targeting only one specific pathogen becomes less effective. Broad-spectrum dispersal of biofilm matrix against multiple Gram-positive genuses, and thereby removing the substrate for future microbial re-colonization and persistent infection, is of great interest for next generation antibiofilm agent development. Wall teichoic acid (WTA), an anionic glycopolymer abundantly present on the cell surface of Gram-positive bacteria, is a highly accessible but underexploited target. We identified that the block co-beta-peptide PDGu-b-PBLK targets WTA of Gram-positive bacteria and potentiates the beta-lactam antibiotic oxacillin against 4 hospital associated MRSA strains. It also disperses the biofilm of all tested Gram-positive bacteria (five species across two genuses). Its cationic block electrostatically interacts with anionic WTA on cell envelope, and the glycosylated block forms a non-fouling corona around the bacteria. This reduces physical interaction of bacteria with biofilm matrix, leading to biofilm dispersal. This co-beta-peptide, which is antibiotic-potentiating, and which disperses biofilms of a broad spectrum of Gram-positive pathogens by targeting a common cell envelope component, WTA, has promising potential for future development of clinical antibacterial and anti-biofilm strategies.